The influence of brand image lifestyle and price on purchasing decisions of voopo brand vape products - Arjun Wijaya; Basar Maringan Hutauruk (Institute of Computer Science (IOCS), 2023)
The purpose of this study is to find out how brand image, lifestyle and price influence consumers' decisions to buy Voopo brand vape products. The type of research used is quantitative. The sampling method used was simple random sampling which amounted to 100 consumers of MAG Vape Store Karawang. Data analysis using SPSS version 25 by performing classical assumption tests, multiple linear regression tests, hypothesis tests and determination coefficient tests. Based on all the tests that have been conducted to determine the influence of brand image on purchasing decisions, it is known that there is a positive and significant influence between brand image on purchasing decisions with a calculated t value of 2.631 greater than t table 1.984, and a sig value of 0.01 smaller than 0.05. Based on all the tests that have been conducted to determine the influence of lifestyle on purchasing decisions, it is known that there is a positive and significant influence between lifestyle on purchasing decisions with a calculated t value of 2.999 greater than t table 1.984, and a sig value of 0.00 smaller than 0.05. Meanwhile, regarding the effect of price on purchasing decisions, the sig result is greater than 0.05, which is 0.457 and the calculated t value of 0.747 is smaller than t table 1.660, so this shows that the price in this study has no effect and is not significant on purchasing decisions. And from the results of the F test it is known that simultaneously there is an influence of brand image, lifestyle and price on purchasing decisions.